Detection of multidrug-resistant bacteria in the eye and face makeup cosmetics collected from local markets of Dhaka - Preety, Shakera Ferdousi; Alam, Fariha; Rahat, Md. Hasan Ibrahim (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2024.